A kinematic model‐based analysis framework for 3D Cine‐DENSE—validation with an axially compressed gel phantom and application in sheep before and after antero‐apical myocardial infarction. Issue 4 (6th June 2021) - Wang, Vicky Y.; Tartibi, Mehrzad; Zhang, Yue; Selvaganesan, Kartiga; Haraldsson, Henrik; Auger, Daniel A.; Faraji, Farshid; Spaulding, Kimberly; Takaba, Kiyoaki; Collins, Alexander; Aguayo, Esteban; Saloner, David; et al.
Abstract : Purpose: Myocardial strain is increasingly used to assess left ventricular (LV) function. Incorporation of LV deformation into finite element (FE) modeling environment with subsequent strain calculation will allow analysis to reach its full potential. We describe a new kinematic model‐based analysis framework (KMAF) to calculate strain from 3D cine‐DENSE (displacement encoding with stimulated echoes) MRI. Methods: Cine‐DENSE allows measurement of 3D myocardial displacement with high spatial accuracy. The KMAF framework uses cine cardiovascular magnetic resonance (CMR) to facilitate cine‐DENSE segmentation, interpolates cine‐DENSE displacement, and kinematically deforms an FE model to calculate strain. This framework was validated in an axially compressed gel phantom and applied in 10 healthy sheep and 5 sheep after myocardial infarction (MI). Results: Excellent Bland–Altman agreement of peak circumferential ( Ecc ) and longitudinal ( Ell ) strain (mean difference = 0.021 ± 0.04 and −0.006 ± 0.03, respectively), was found between KMAF estimates and idealized FE simulation. Err had a mean difference of −0.014 but larger variation (±0.12). Cine‐DENSE estimated end‐systolic (ES) Ecc, Ell and Err exhibited significant spatial variation for healthy sheep. Displacement magnitude was reduced on average by 27%, 42%, and 56% after MI in the remote, adjacent and MI regions, respectively. Conclusions: The KMAF framework allows accurate calculation of 3D LV Ecc and Ell from cine‐DENSE.